2020
DOI: 10.3390/educsci10110345
|View full text |Cite
|
Sign up to set email alerts
|

Responding to Global Learning Needs during a Pandemic: An Analysis of the Trends in Platform Use and Incidence of COVID-19

Abstract: On 11 March 2020, the World Health Organization (WHO) declared the outbreak of coronavirus disease (COVID-19) to be a pandemic. As a result, the OpenWHO.org online platform, which serves as WHO’s learning hub for emergencies, was tested for the first time on its core purpose of scaling up trusted public health information in a global emergency. This descriptive study examines and documents the WHO learning response in the early months of the pandemic by comparing epidemiological information and OpenWHO.org use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Offline options increase access even further. 3. Flexibility: self-paced mass web-based learning delivery enables individuals to learn at their own speed, at their preferred time, and in their preferred place.…”
Section: Core Benefits Of the Massive Web-based Learning Formatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Offline options increase access even further. 3. Flexibility: self-paced mass web-based learning delivery enables individuals to learn at their own speed, at their preferred time, and in their preferred place.…”
Section: Core Benefits Of the Massive Web-based Learning Formatsmentioning
confidence: 99%
“…Several findings derived from the analysis of the performance of the OpenWHO platform during the pandemic are presented herein, with regards to the global reach of the courses [1], growth in the uptake of OpenWHO's web-based learning resources [2], and trends in platform usage and the incidence of COVID-19 [3].…”
Section: Introductionmentioning
confidence: 99%
“…In three articles, digital learning approaches were claimed to be more effective than no intervention in improving knowledge [43,44,48] or at least as effective as traditional learning [48]; yet one systematic review suggested that e-learning may make little or no difference in patient outcomes or health professionals' behaviours, skills or knowledge [49]. Moreover, knowledge level was also examined by two crosssectional studies conducted in Germany, and Italy, one case study in Portugal, and one evaluation of a massive open online course (MOOC) [9,[52][53][54]. Authors reported an improvement of knowledge level [53,54] as well as participants of these interventions reported utilization of the knowledge [31], and skills gained in their professional lives frequently [9].…”
Section: Phase 1 Results: Overview Of the Examined Literaturementioning
confidence: 99%
“…Moreover, knowledge level was also examined by two crosssectional studies conducted in Germany, and Italy, one case study in Portugal, and one evaluation of a massive open online course (MOOC) [9,[52][53][54]. Authors reported an improvement of knowledge level [53,54] as well as participants of these interventions reported utilization of the knowledge [31], and skills gained in their professional lives frequently [9]. Previous research on the effectiveness of digital learning for knowledge acquisition in health professionals confirmed that either online or blended learning had a more consistent positive effect than no intervention or traditional learning [17][18][19][20].…”
Section: Phase 1 Results: Overview Of the Examined Literaturementioning
confidence: 99%
“…As of 2 March 2021, twenty-six countries still face nation-wide school closures, and many others have partial closures limiting access to educational settings to about 8.3% of all learners. Even in countries where physical access to schools has been reinstated, educational settings face the challenge of providing quality educational services while following public health measures aimed at containing the spread of the virus [2][3][4][5]. The adoption of remote teaching and learning practices in various countries highlighted at least two major challenges for schools: an internal misalignment between previous experiences and available resources, and the need for new online education practices.…”
Section: Introductionmentioning
confidence: 99%